Produksi Bioetanol Dari Sari Kulit Nenas Menggunakan Yeast Saccharomyces Cerevisiae Dengan Variasi Penambahan Tween 80 Dan Sumber Nitrogen - Sheilviana Angela; Sri Rezeki Muria; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
One material that has potential to be used as raw material for bioethanol is the pineapple peel. Pineapple peel from the pineapple is one of the biggest agricultural waste in Indonesia, particulary in the area of Riau. Pineapple peel can be used as raw material for bioethanol production because contain much fibers, carbohydrates and glucose. This study aimed to obtain the highest amount of bioethanol from fermented juice pineapple peel using the yeast Saccharomyces cerevisiae by varying the concentration of tween 80 and comparing the nitrogen sources such as peptone and yeast extract and fermentation time is 24, 48 , 72, 96, and 120 hours. Measurement of bioethanol content using alcoholmeter. From the research results, obtained the highest bioethanol content of 9% v/v or 71,04 mg/ml in the additions at 20 ml tween 80 and a nitrogen source such as peptone and the fermentation time 96 hours.Keywords: Bioethanol, Pineapple Peel, Pepton, Saccharomyces cerevisiae, Tween 80, Yeast Extract